2020
DOI: 10.1038/s41598-020-79083-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-flux scanning electron diffraction reveals substructures inside the ordered membrane domain

Abstract: Ordered/disordered phase separation occurring in bio-membranes has piqued researchers’ interest because these ordered domains, called lipid rafts, regulate important biological functions. The structure of the ordered domain has been examined with artificial membranes, which undergo macroscopic ordered/disordered phase separation. However, owing to technical difficulties, the local structure inside ordered domains remains unknown. In this study, we employed electron diffraction to examine the packing structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Then, these clusters (substructures or subdomains) may serve as the platform for the DChl superlattice observed in the present study. Note in this respect that, recently, Kinoshita and co-workers, using the electron diffraction technique, found that the ordered domain in the membrane contains multiple subdomains with different crystallographic axes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Then, these clusters (substructures or subdomains) may serve as the platform for the DChl superlattice observed in the present study. Note in this respect that, recently, Kinoshita and co-workers, using the electron diffraction technique, found that the ordered domain in the membrane contains multiple subdomains with different crystallographic axes.…”
Section: Discussionmentioning
confidence: 97%
“…17−19 However, despite the extensive literature about the cholesterol−lipid interactions in lipid membranes, direct experimental information on the molecular structure of lipid and cholesterol assemblies remains scarce. 15,20,21 Moreover, controversies about the properties, composition, and even the very existence of lipid rafts remain unresolved. 20 Double electron−electron resonance spectroscopy (DEER, also known as PELDOR) allows studying nanoscale spatial structures of spin-labeled molecules and their assemblies.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subphase temperature and ambient temperature were kept at 25.0 ± 0.1 and 25 ± 1 °C, respectively. The measurements were repeated thrice under the same conditions to obtain reliable data …”
Section: Methodsmentioning
confidence: 99%
“…The measurements were repeated thrice under the same conditions to obtain reliable data. 34 Molecular Dynamics Simulation. The ginsenoside Rh2 molecule was built based on the reported X-ray structure of ginsenoside compound K (20-O-β-glucopyranosyl-20(S)-protopanaxadiol) 35 and parametrized using the CHARMM General FF 36 based on the CHARMM36 lipid force field 37 and carbohydrate force fields and the previously reported cholesteryl-β-glucopyranoside (ChoGlc).…”
Section: ■ Introductionmentioning
confidence: 99%